Factors Affecting Student's Interest in Learning in Online Learning in Elementary School - Setiawan, Tri Yudha; Frimals, Aeron; Vandera, Dea; Ningrum, Dessya Mas; Effendi, Rendi Nur; Istiqomah, Lailatul (IJECA (International Journal of Education and Curriculum Application), 2022)
The aim of this study was to find out what factors influence students' interest in learning in online learning. The approach in this research is qualitative and the type of research is a case study. The qualitative method was chosen to describe what factors influence students' interest in learning when learning online at Elementary School. The collection in this study uses humans as an instrument (human instruments). Data collection techniques using interviews and observation. Informants in this study were teachers, students, and parents. Based on the results found in this study, it shows that the factors that influence students' interest in learning consist of two factors, namely internal factors and external factors. Internal factors are the interest of students in learning, the convenience of students in learning, the readiness of students in learning, and the ability to use technology in learning. External factors are family support, student learning facilities and learning atmosphere.